Comparison of Zirconia and Lithium Disilicate Crowns: A Randomized Controlled Trial on Longevity and Patient Satisfaction - Mehwish Urooj, Fahad Salim Khan , Affan Ahmad , Hamna Khawaja, Laiba Shoaib, Amnah Mehwish Ikram , Farah Naz (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
The comparison of zirconia and lithium disilicate crowns in terms of longevity and patientsatisfaction represents an important aspect of restorative dentistry. Both materials have gainedpopularity due to their excellent esthetics and strength; however,